Analysis of two heat storage integrations for an Organic Rankine Cycle Parabolic trough solar power plant. (1st October 2016) - Chacartegui, R.; Vigna, Leo; Becerra, J.A.; Verda, V.
Highlights: Thermal storage Solar Parabolic Trough integrated with Organic Rankine Cycle. Small Parabolic Trough Direct/Indirect thermal storage layouts integration. Full system performance analysis at design and off design conditions. Best result for 10 h of storage with Levelized Cost of Electricity 16.3 c€/kW. Application in off-grid and distributed generation (as mines). Abstract: Among the concentrated solar power technologies, those based on Organic Rankine Cycles have a very low market presence. However they have favorable characteristics for applications with low temperature and small/medium size (<10 MW), such as off-grid applications or distributed power generation. In this paper is analyzed a 5 MW parabolic trough plant integrated with an Organic Rankine cycle power block and thermal storage. On this purpose, two different thermal storage integrations are analyzed. They are based on two different heat storage layouts: direct system using Hitec XL both as Heat Transfer Fluid and as storage medium; indirect system using Therminol VP-1 as Heat Transfer Fluid and Hitec XL as storage medium. Full system performance at rated and off-design conditions is presented operating with different organic working fluids. Its potential application and main challenges for its development are discussed in terms of performance and costs. Among the analyzed working fluids, the best results were obtained for the cycle working with Toluene with an efficiency at the power block of 31.5% and an estimated power block cost of 825 €/kW. The indirect storage layout was the most interesting from the point of view of Levelized Electricity Cost (16.19 c€/kW) and productivity (28.2 GW h/y for a 5 MWel plant) for 10 h of storage However, it results in a storage tanks volume 26% greater than the obtained for the equivalent direct storage layout. The results show the competitiveness and the potential of the proposed integrated small size parabolic trough designs for isolated applications as mines or for some distributed generation uses where grid capacity is limited.